Self-Efficacy, Core Behavioral Competence and Performance of Teachers: A Scaffold for Proficient and Highly Proficient Teachers - Bantoc, Aris A.; Yazon, Alberto D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This research aimed to determine the relationship between self-efficacy, core behavioral competence and level of performance among Public Elementary and Secondary School teachers in two (2) Districts in Mauban, Division of Quezon. The following hypotheses were tested in this study (a) there is no significant relationship between teacher's level of self-efficacy, core behavioral competence and performance among public elementary and secondary school teachers in Mauban District; and (b) teacher's self-efficacy and core behavioral competencies do not significantly predict their level of performance. A descriptive quantitative research design was used in this study, incorporating descriptive survey, correlation, comparative and causal-comparative methods to answer the specific research problems. The study's respondents were the 247 public elementary and secondary proficient and highly proficient teachers from 39 schools of the two districts in Mauban, Quezon – the Mauban North District and Mauban South District. A stratified random sampling technique was used in selecting the teachers-respondents. A 45-item Likert scale survey questionnaire, the main research instrument, was used. This study found no significant difference in the teachers' self-efficacy and core behavioral competence when grouped according to their number of teaching/ ancillary load, highest educational attainment, number of years in service and teaching position. The level of self- efficacy in practicing the PPST domains and teachers' performance level has a strongly positive correlation. Likewise, the level of core behavioral competence in practicing the PPST domains and the level of performance have a strong positive correlation. Regarding the strength of the relationship, there is a strong positive correlation between teachers' self-efficacy and core behavioral competence on the overall teachers' performance. The predicting capacity of self-efficacy and core behavioral competence to the overall performance of teachers is statistically significant. Self-efficacy and core behavioral competencies are predictors of teachers' performance. The higher the teachers' self-efficacy level, the better their performance; the higher the core behavioral competence, the higher their performance.